Decompressive craniectomy versus conservative treatment: limits and possibilities in malignant stroke - Isaac Holanda Mendes MAIA; Thaissa Pinto de MELO; Fabrício Oliveira LIMA; João José de Freitas CARVALHO; Francisco José Arruda MONT’ALVERNE; Edson LOPES JÚNIOR; Marcelo Bezerra DIÓGENES; Thaís Saraiva Leão CUNHA; Bárbara Matos Almeida QUEIROZ; Marina Franciss TAMIETTI; Fernanda Martins MAIA (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Malignant infarction of the middle cerebral artery (MCA) occurs in a subgroup of patients with ischemic stroke and early decompressive craniectomy (DC) is one of its treatments. Objective: To investigate the functional outcome of patients with malignant ischemic stroke treated with decompressive craniectomy at a neurological emergency center in Northeastern Brazil. Methods: Prospective cohort study, in which 25 patients were divided into two groups: those undergoing surgical treatment with DC and those who continued to receive standard conservative treatment (CT). Functionality was assessed using the modified Rankin Scale (mRS), at follow-up after six months. Results: A favorable outcome (mRS≤3) was observed in 37.5% of the DC patients and 29.4% of CT patients (p=0.42). Fewer patients who underwent surgical treatment died (25%), compared to those treated conservatively (52.8%); however, with no statistical significance. Nonetheless, the proportion of patients with moderate to severe disability (mRS 4‒5) was higher in the surgical group (37.5%) than in the non-surgical group (17.7%). Conclusion: In absolute values, superiority in the effectiveness of DC over CT was perceived, showing that the reduction in mortality was at the expense of increased disability.